2018
DOI: 10.1002/jsfa.8835
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic changes of the porcine skeletal muscle in response to chronic heat stress

Abstract: The results indicate that HS-induced changes in the expression of myofibrillar proteins, glucose and energy metabolism-related proteins, heat shock protein and antioxidant enzymes might, at least partly, contribute to increase in meat tenderness. These findings will provide the foundation for developing future mitigating solutions and preventative therapies to reduce the detrimental effects of chronic HS on muscle function, metabolism and meat quality. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 41 publications
(48 reference statements)
1
6
1
1
Order By: Relevance
“…Any deviation of the normal pH rate could lead to poor meat quality, producing PSE or DFD (dark, firm and dry) meat, in cases of low or high pH values at 24 h p.m., respectively [ 5 ]. Conversely to our results, higher lightness (paler color) and lower a* and b* values have been found as effects of high temperature exposure in muscles of lean pigs [ 11 , 30 , 40 ], which has been attributed to the muscle oxidative status and the gradual transformation of the different states of the pigment myoglobin, the principle responsible for meat color, that is very sensitive to oxidation [ 41 ]. Discoloration of muscles results from oxidation of both ferrous myoglobin derivatives to ferric iron of metmyoglobin [ 41 ] and therefore, no occurrence of pale color could indicate a higher protection against oxidation in HS muscles (as discussed below).…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…Any deviation of the normal pH rate could lead to poor meat quality, producing PSE or DFD (dark, firm and dry) meat, in cases of low or high pH values at 24 h p.m., respectively [ 5 ]. Conversely to our results, higher lightness (paler color) and lower a* and b* values have been found as effects of high temperature exposure in muscles of lean pigs [ 11 , 30 , 40 ], which has been attributed to the muscle oxidative status and the gradual transformation of the different states of the pigment myoglobin, the principle responsible for meat color, that is very sensitive to oxidation [ 41 ]. Discoloration of muscles results from oxidation of both ferrous myoglobin derivatives to ferric iron of metmyoglobin [ 41 ] and therefore, no occurrence of pale color could indicate a higher protection against oxidation in HS muscles (as discussed below).…”
Section: Resultscontrasting
confidence: 99%
“…Exposure to high temperatures in pigs has been usually associated with a deterioration of meat quality and occurrence of PSE (pale, soft, exudative) meat, with decreased pH values, pale color and increased drip losses [ 4 , 11 , 39 , 40 ], which has been explained by a stimulation of muscle glycogenolysis and further metabolic acidosis under heat conditions. However, increased values of ultimate pH have also been observed in other heat stress assays [ 12 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…We found that the concentrations of serum non-esterified fatty acid (NEFA), including myristic acid, palmitic acid, and linoleic acid were significantly increased in the HS group, which is in line with the findings in dairy cows [30]. These results could be supported by our previous finding of decreased intramuscular fat proportion due to HS [38], suggesting stronger lipid decomposition for energy generation. A schematic presentation of some changed metabolic pathways is shown in Figure 5.…”
Section: Discussionsupporting
confidence: 89%
“…In general, IMP is thought to have a synergistic effect on taste [28]. IMP contributes mostly to Compared with our previous study on proteomic changes of the LD muscle in response to chronic heat stress, most of the proteins are involved in carbohydrate metabolism, myofibrillar and cytoskeleton structure, stress response, antioxidant and detoxification, calcium binding, and cellular apoptosis [27]. Among them, glycogen phosphorylase (PYGM), superoxide dismutase (Cu-Zn) (SOD1), and succinyl-CoA synthetase beta-A chain (SCSLA2) were respectively involved in the glucagon signaling pathway (KEGG ID ssc04922), insulin resistance pathway (KEGG ID ssc04931), peroxisome pathway (KEGG ID ssc04146), and peroxisome proliferator activated receptor (PPAR) signaling pathway (KEGG ID ssc03320).…”
Section: The Effect Of Heat Stress On the Contents Of Meat Quality-rementioning
confidence: 78%
“…According to the results of our previous study, HS increased the abundance of proteins involved in stress response, disrupted the pro-oxidant/antioxidant balance, and affected meat quality of finishing pigs [27].…”
Section: The Effects Of Heat Stress On Muscle Metabolites Related To mentioning
confidence: 84%